Detection of Delafloxacin Resistance Mechanisms in Multidrug-Resistant Klebsiella pneumoniae - András Kubicskó; János Juhász; Katalin Kamotsay; Dora Szabo; Béla Kocsis (Antibiotics)
Background: In this study, the mechanisms implicated in delafloxacin resistance in Klebsiella pneumoniae strains were investigated. Delafloxacin is a novel, broad-spectrum fluoroquinolone that has been approved for clinical application. Methods: In our study, 43 K. pneumoniae strains were assessed, antimicrobial susceptibility testing was performed via the broth microdilution method, and the minimum inhibitory concentration (MIC) values for ciprofloxacin, delafloxacin, levofloxacin, moxifloxacin, ceftazidime, cefotaxime, and imipenem were determined. Four delafloxacin-resistant K. pneumoniae strains were selected for whole-genome sequencing (WGS). Results: The MIC50 values for the 43 K. pneumoniae strains were as follows: ciprofloxacin 0.5 mg/L, levofloxacin 0.25 mg/L, moxifloxacin 0.5 mg/L, and delafloxacin 0.25 mg/L. All four selected delafloxacin-resistant K. pneumoniae strains showed extended-spectrum beta-lactamase production, and one strain exhibited carbapenem resistance. WGS enabled us to determine the sequence types (STs) of these strains, namely, ST307 (two strains), ST377, and ST147. Multiple mutations in quinolone-resistance-determining regions (QRDRs) were detected in all the delafloxacin-resistant K. pneumoniae strains; specifically, gyrA Ser83Ile and parC Ser80Ile were uniformly present in the strains of ST307 and ST147. However, in the ST377 strain, gyrA Ser83Tyr, Asp87Ala, and parC Ser80Ile, amino acid substitutions were detected. We also identified OqxAB and AcrAB efflux pumps in all delafloxacin-resistant K. pneumoniae strains. The association between beta-lactamase production and delafloxacin resistance was determined; specifically, CTX-M-15 production was detected in the ST147, ST307, and ST377 strains. Moreover, NDM-1 was detected in ST147. Conclusions: We conclude that multiple mutations in QRDRs, in combination with OqxAB and AcrAB efflux pumps, achieved delafloxacin resistance in K. pneumoniae. In our study, we report on NDM-1-producing K. pneumoniae ST147 in Hungary.